(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In today’s digital landscape, organizations leveraging Pega Business Process Management (BPM) face significant security challenges as they strive to protect sensitive business processes from evolving cyber threats. This article explores best practices for implementing robust security measures within Pega BPM environments, focusing on secure configuration settings, identity and access management (IAM), encryption standards, and real-time monitoring. By integrating Pega BPM with broader cybersecurity frameworks, organizations can proactively detect and mitigate vulnerabilities, ensuring the integrity and confidentiality of critical business operations. This research highlights the importance of a holistic approach to security, combining technical measures with organizational policies to create a resilient BPM environment. Through a detailed examination of methodologies, implementation strategies, and performance evaluations, this article provides actionable insights for organizations aiming to strengthen their security posture. The findings underscore the necessity of continuous monitoring, adaptive security configurations, and alignment with industry standards to address emerging threats effectively. This study contributes to the field by identifying research gaps and offering practical recommendations for securing Pega BPM systems in an increasingly complex threat landscape.